Efek panas pada besi dan stainless steel 304 untuk penyaring udara mesin incinerator - Agung Sudrajad; Muhammad Rafli Gumay Putra; Sunardi (Jurnal Teknik Mesin Indonesia, 2023)
Particulate matter in the environment can give a bad effect to the body of human through the respiratory process. These conditions require researchers to innovate to reduce the air pollution. The electrostatic precipitator (ESP) filter system is one technology for reduce of particulate matter by the combustion of Incinerator. This system has a good efficiency and very good in reducing of particulate matter produce by Incinerator. The materials used for the ESP system air filter in this study were iron and Stainless Steel 304. The tests carried out were the corrosion rate test, and X-Ray Diffraction (XRD) where the corrosion rate of the material will be measured using the weight loss method and seen the content and elements involved. changed using XRD. The results shows that the corrosion rate test, iron has a corrosion rate decrease of 66% and Stainless Steel 304 by 73%.. The Scanning Electron Microscope (SEM) EDX results show that after heating both specimens have the same ferrite pearlite phase but for iron specimens, pearlite is more dominant, and stainless steel 304 is more dominant in ferrite. While for the XRD results, there are wave changes on the graph of the iron and stainless steel 304 specimens before and after being heated, which means that there are differences in the phase of the two specimens.